Lethal Concentration and Lethal Time Botanical Insecticide Tuba Root Extract Against Spodoptera frugiperda J. E. Smith Larvae - Ibrahim, Mukhlis; Rustam, Rusli (Journal of Applied Agricultural Science and Technology, 2024)
Utilization of botanical insecticides is an option to control environmentally friendly Spodoptera frugiperda  pests. The purpose of this study was to determine the lethal concentration (LC) and lethal time (LT) of botanical insecticides on the third instar larvae of S. frugiperda in the laboratory. The experiment was conducted at the Applied Entomology Laboratory, Faculty of Agriculture, Gadjah Mada University, Yogyakarta, over a period of 3 months, from September to November 2022. The concentration treatments used were 0, 2, 4, and 8 ml/L of water. The experiment was designed using a completely randomized design (CRD) with 4 treatments and 5 replications. Larval mortality data was processed using probit analysis in order to determine the value of Lethal Concentration (LC50 and LC95) and Lethal Time 50 (LT50). The results showed that the tuba root powder extract concentration showed LC50 and LC95 namely 0.07% equivalent to 0.7 ml/L of water and 1.53% equivalent to 15.3 ml/L of water. Meanwhile the concentration of 8 ml/L of water extract of tuba root flour causes LT50 of S. frugiperda larvae causing time to tend to be faster at 1.86 days or 44,64 hours after application. Botanical insecticides of the tuba root extract concentration show high efficacy against S. frugiperda larvae so that they can be recommended as a component for integrated pest management (IPM).